Determining and testing the accuracy of incubation stage of Ruddy Duck eggs by floatation - Brua, Robert B; Machin, Karen L (Wildfowl, 2000)
An egg floatation model was developed for determining the incubation stage of Ruddy Duck (Oxyura jamaicensis) eggs, and the accuracy of this model was then tested by correlating actual incubation age against the incubation age predicted from the egg floatation model. A strong positive correlation existed between actual incubation age and predicted age suggesting that model accuracy was high. Also, predicted incubation age was ltoreq two days of actual incubation age on 84% of the occasions and within three days 93% of the time. We consider floating Ruddy Duck eggs to be an accurate and practical alternative to field candling and encourage others to develop and test egg floatation models for difficult-to-candle avian species.